Herlyn-Werner-Wunderlich syndrome: Case report - Laura Catalina López-Alza; Mario Santiago Mesa-Espinel (Revista de la Facultad de Medicina, 2021)
Introduction: Herlyn-Werner-Wunderlich (HWW) syndrome is a rare congenital malformation of the urogenital tract characterized by the triad of uterine didelphys, obstructed hemivagina, and ipsilateral renal agenesis, which is usually diagnosed after menarche. It is treated by resecting the vaginal septum and draining the obstructed hemivagina and has a favorable postoperative prognosis.